STIMULASI PERTUMBUHAN AWAL BENIH MELON (Cucumis melo L.) MELALUI SKARIFIKASI DAN GIBERELIN - Rahmatika, Widyana; Fitriyah, Nur; Imadudin, Alfiyan (BUANA SAINS, 2024)
The aim of this study was to determine the effect of scarification and gibberellin soaking on seed stimuli in melon. The study used a factorial randomized block design with two treatment factors. The first treatment factor, mechanical interruption of seed dormancy (F), consisted of two treatments: F1 = control (no treatment) and F2 = seed scarification, while the second treatment factor, ZPT gibberellin soaking (G), consisted of four levels: G1 = 0 ppm gibberellin, G2 = 20 ppm gibberellin, G3 = 40 ppm gibberellin, and G4 = 40 ppm gibberellin. The parameters observed were the early vegetative growth of melon, i.e. plant height (cm) and number of leaves (stems). The results showed that The results showed that interaction occurred due to the scarification treatment and Gibberellin soaking, with the best results brought by the scarification treatment with a Gibberellin concentration of 30 ppm on the parameters of plant height and number of leaves.